2014
DOI: 10.1136/bjsports-2013-093014
|View full text |Cite
|
Sign up to set email alerts
|

Associations of overall sitting time and TV viewing time with fibrinogen and C reactive protein: the AusDiab study

Abstract: Overall sitting time was positively associated with plasma fibrinogen and hsCRP in men and women; associations of TV viewing time with fibrinogen were observed in women only. Abdominal adiposity-mediated associations for hsCRP but not for fibrinogen. Prospective and intervention studies are needed to establish likely causality and elucidate potential mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 30 publications
(33 reference statements)
7
42
2
1
Order By: Relevance
“…In fact, the National Health and Nutrition Examination Survey (NHANES) study 13 observed a positive relation of sedentary behavior with glucose levels and negative relationship with HDL-C levels. Similar results were also observed in the AusDiab study 32 and EPIC-Norfolk study 37 . Review study 36 has suggested that prolonged uninterrupted periods of being sedentary results in insufficient skeletal muscle contractions, which suppresses lipoprotein lipase activity, blunts triglyceride uptake, reduces HDL-C levels and glucose load, and increases insulin resistance.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In fact, the National Health and Nutrition Examination Survey (NHANES) study 13 observed a positive relation of sedentary behavior with glucose levels and negative relationship with HDL-C levels. Similar results were also observed in the AusDiab study 32 and EPIC-Norfolk study 37 . Review study 36 has suggested that prolonged uninterrupted periods of being sedentary results in insufficient skeletal muscle contractions, which suppresses lipoprotein lipase activity, blunts triglyceride uptake, reduces HDL-C levels and glucose load, and increases insulin resistance.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results were also observed in older adults, diabetics and obese 12-14, 32 , which shows the negative impact of sedentary behavior on inflammation in patients with different clinical conditions. In PAD patients, high HsCRP levels have been associated with progression of disease and cardiovascular mortality 33 .…”
Section: Discussionsupporting
confidence: 82%
“…This is supported by the findings from several prospective studies which have shown that higher levels of inflammatory markers and their soluble receptors are associated with accelerated losses in muscle mass and strength [38,39]. While there are some reports that increased sitting time is directly associated with an increase in circulating inflammatory markers [10,40,41], after adjusting for BMI, these associations tended to be attenuated or became nonsignificant [10,42]. This suggests that increased adiposity associated with greater sedentary time may be driving any increase in inflammation which may in turn contribute to muscle loss, but further studies are needed to address this question.…”
Section: Discussionsupporting
confidence: 64%
“…19,20 For example, in over 3,000 Australian adults TV time was associated with CRP and fibrinogen although after adjustment for waist circumference these relationships were attenuated to the null. 19 In a small study of 285 adults, changes in sedentary time over 6 months were associated with CRP in women, although no associations were observed with other biomarkers, including adiponectin, soluble intracellular adhesion molecule-1, and interleukin-6. 32 In a longitudinal cohort study baseline TV viewing time was not significantly associated with change in metabolic biomarkers over 5 years follow-up although inflammatory markers were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] However, there are a paucity of longitudinal data. We recently demonstrated an association between TV viewing (aged 23) and inflammatory markers at follow up (aged 44) in a birth cohort study but were unable to infer true changes over time since biomarkers were not collected at baseline.…”
Section: Introductionmentioning
confidence: 99%